(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This research article analyzes several aspects of improving the effectiveness of law enforcement agencies in Uzbekistan and introducing a system of openness and transparency. Establishing a dialogue with the public and implementing new information and communication technologies strengthen citizens’ trust in this institution. Along with all the positive trends, many problems and shortcomings in Uzbekistan’s internal affairs system are also examined. The analysis and research yield scientifically sound conclusions.